2012
DOI: 10.1371/journal.pone.0047741
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Astroglial Rictor Overexpression Induces Malignant Glioma in Mice

Abstract: BackgroundHyperactivation of the mTORC2 signaling pathway has been shown to contribute to the oncogenic properties of gliomas. Moreover, overexpression of the mTORC2 regulatory subunit Rictor has been associated with increased proliferation and invasive character of these tumor cells.Methodology/Principal FindingsTo determine whether Rictor overexpression was sufficient to induce glioma formation in mice, we inserted a Cre-lox-regulated human Rictor transgene into the murine ROSA26 locus. This floxed Rictor st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 53 publications
1
45
1
Order By: Relevance
“…We and others (3,4) have demonstrated increased expression of Rictor in GBM. This results in hyperactivated mTORC2 signaling leading to accelerated GBM growth, motility, and invasive characteristics (3,5).…”
Section: Glioblastomas (Gbm)mentioning
confidence: 99%
See 2 more Smart Citations
“…We and others (3,4) have demonstrated increased expression of Rictor in GBM. This results in hyperactivated mTORC2 signaling leading to accelerated GBM growth, motility, and invasive characteristics (3,5).…”
Section: Glioblastomas (Gbm)mentioning
confidence: 99%
“…In this study, we utilized a recently developed GEM model, in which glial fibrillary acidic protein Cre (Gfap-Cre)-mediated conditional Rictor overexpression induced intermediate grade gliomas (5). Using a retroviral gene-trapping strategy to identify modifiers that accelerate transformation and growth of cell lines derived from gliomas from these mice, we identified AMOTL2 as a relevant signaling node linking mTOR complex 2 (mTORC2) signaling and the Hippo pathway.…”
Section: Glioblastomas (Gbm)mentioning
confidence: 99%
See 1 more Smart Citation
“…Blocking Rictor phosphorylation, which was able to lessen the inhibition of the mTORC2-Akt signaling pathway, was applied to stop tumor progression and cancer cell proliferation (17). Bashir et al reported that the Rictor gene was involved in cancer cell proliferation in malignant glioma and had a high recurrence rate in hepatic carcinoma (18). A previous study indicated that integrin-linked kinase (ILK), a focal adhesion adaptor, is an STK that regulates cell proliferation, survival and EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in mice also reported that over expression of RICTOR gene was associated with increased proliferation of cells along with invasion of tumor cells (Bashir et al, 2012). Mammalian TORC2 plays a role in actin cytoskeleton reorganization and similar to yeast TORC2, the Rho-type GTPases were involved in these functions.…”
Section: Histopathology Of Visceral Organsmentioning
confidence: 96%